Maritime Geostrategy: Managing Risks and Opportunities in the Strait of Malacca as a Primary International Supply Chain Route - Toelihere, Ivan Filbert; Lukman Yudho Prakoso; Endro Legowo (Cita konsultindo, 2025)
The This research analyzes the risks, opportunities, management strategies, and the role of maritime geostrategy in the management of the Strait of Malacca as a primary international supply chain route. The findings indicate that the Strait of Malacca faces significant maritime security threats, traffic congestion, and impacts from climate change, which affect the stability of maritime transportation. Risk management strategies through UNCLOS, ReCAAP, and the Malacca Straits Patrol have proven effective but still face operational challenges. Strategic opportunities are identified through the development of port infrastructure and the adoption of modern logistics technology. Geopolitical dynamics between coastal states and major powers, such as the US and China, influence regional stability and the sustainability of the global supply chain. This study recommends multilateral collaboration, sustainable investment in infrastructure, and the adoption of technology to enhance the efficiency and security of maritime transportation. With a holistic approach, the Strait of Malacca can continue to play its role in supporting an efficient and sustainable international supply chain.